Do leaders affect ethical conduct? - Giovanna D'Adda; Donja Darai; Roberto A. Weber (University of Zurich, Department of Economics, 2014)
We study whether leaders influence the unethical conduct of followers. To avoid selection issues present in natural environments, we use a laboratory experiment in which we form groups and assign leadership roles at random. We study an environment in which groups compete, with dishonest behavior enhancing group earnings to the detriment of social welfare. We vary, by treatment, two instruments through which leaders can influence follower conduct-prominent statements to the group and the allocation of monetary incentives. In general, the presence of active group leaders gives rise to significantly more dishonest behavior. Moreover, appointing leaders who are likely to have acted dishonestly in a preliminary stage of the experiment yields groups with significantly more unethical conduct. The analysis of leaders' strategies reveals that leaders' statements have a stronger effect on follower behavior than the ability to distribute financial rewards, and that leaders' propensity to act dishonestly correlates with their use of statements or incentives as a means for encouraging dishonest follower conduct.
Keywords: C92; C72; D03; 330; leadership; ethics; dishonesty; experiment